THE ROLE AND STATUS OF DIGITAL FORENSIC EXPERIENCES IN ANALYZING DIGITAL EVIDENCE ON THE EVIDENCE OF CYBERCRIME CRIMINAL ACTION IN NORTH SUMATERA POLDA - Zulkifli Zulkifli; Marlina Marlina; Adil Akhyar (LPPM YPITI, 2021)
With regard to proving cybercrime, digital forensic or digital forensic laboratories are urgently needed, which aims to investigate and establish facts relating to criminal incidents and other legal issues. As for the problems in this study, namely: What is the legal arrangement of evidence in proving cyber crime? What is the authority of digital forensic experts in uncovering digital evidence on cyber crime? What are the obstacles found by digital forensic experts in the process of proving cyber crime?This type of research is empirical juridical research, while the nature of the research is descriptive analysis. This research uses several approaches, namely the law and conceptual approach. Research data sources consist of primary and secondary data. The data analysis used in this study is qualitative data analysis. Based on the results of the research, the evidence in proving cyber crime is obtained from electronic evidence in the form of electronic information and/or electronic documents relating to criminal acts. The collection of electronic evidence is carried out by the implementation of digital forensics by the North Sumatra Regional Police digital forensic expert. Electronic evidence, so that it can be used as electronic evidence and become legal evidence in evidence in court by meeting formal and material requirements as legal evidence. The authority of digital forensic experts relates to their position and function to explain and explain electronic evidence that is used as digital evidence in the process of proving cybercrime criminal cases as regulated in Article 184 paragraph (1) of the Criminal Procedure Code jo Article 5 paragraph (2) of the ITE Law. The obstacles of digital forensic experts in uncovering cybercrime cases include the nature of electronic evidence which is very vulnerable, because it is easily changed, deleted, or hidden by the culprit. Human resources who understand digital forensic are still weak, inadequate facilities and infrastructures and very limited budget.